Early Detection Of Chronic Diseases With Blood Pressure And Blood Sugar Level Checking In The Elderly: A Community-Based Intervention - witriyani (Bhakti Sabha Nusantara, 2025)
Aging is a natural process that occurs throughout human life. Physiologically, aging causes a decline in the function of various organs, making them susceptible to both acute and chronic non-communicable diseases. Furthermore, degenerative conditions can weaken the immune system, making them susceptible to infectious diseases. Diabetes mellitus and hypertension are common chronic conditions. This community service activity targets the elderly in the Banaran Grogol village of Sukoharjo. It is hoped that this activity will raise community awareness about chronic disease management. The solution proposed by this community service team (PKM) involves measuring blood pressure, checking blood sugar levels at any time, counseling regarding examination results, healthy lifestyle information and recognizing early signs of chronic diseases. The implementation of this community service activity was carried out at the Kenangan VI Banaran Posyandu, Grogol, Sukoharjo, which was attended by the village head, village midwife, Grogol Health Center Health Team, 16 Posyandu cadres, 55 elderly people and 6 community service team members consisting of 2 lecturers and 4 nursing students.